Process philosophy's potential contributions to innovation process research within organization studies - Queila Regina Souza Matitz; Karine Francisconi Chaerki (Innovation & Management Review, 2018)
Purpose: The purpose of this paper is to discuss process philosophy's potential contributions to understanding and investigation of innovation processes associated with organizational contexts. Design/methodology/approach: The paper is a theoretical piece that examines the concept of process philosophy by relating it to the relevant literature and use of examples. Findings: In particular, the authors develop some ideas and encourage future discussion around two aspects: process philosophy-oriented conceptualizations of innovation processes and process philosophy-oriented methods of investigation about innovation processes. The authors conclude that more process philosophy-oriented research of innovation processes must be conceptually multidimensional and methodologically performative. Originality/value: There is a recent claim about a "process turn" within organization studies, which is partly represented by attempts to develop and apply a deeper meaning of process. The presentation of the concept is novel, and does add to the literature. These aspects provide clarification regarding implications of thinking and enquiring procedurally into innovation processes.
Keywords: 650; Research